Human Amnion-Derived Mesenchymal Stem Cells Promote Osteogenic Differentiation in Human Bone Marrow Mesenchymal Stem Cells by Influencing the ERK1/2 Signaling Pathway - Yuli Wang; Fei Jiang; Yi Liang; Ming Shen; Ning Chen (Stem Cells International)
Human amnion-derived mesenchymal stem cells (HAMSCs) are considered to be an important resource in the field of tissue engineering because of their anti-inflammatory properties and fewer ethical issues associated with their use compared with other sources of stem cells. HAMSCs can be obtained from human amniotic membranes, a readily available and abundant tissue. However, the potential of HAMSCs as seed cells for treating bone deficiency is unknown. In this study, HAMSCs were used to promote proliferation and osteoblastic differentiation in human bone marrow mesenchymal stem cells (HBMSCs) in a Transwell coculture system. Proliferation levels were investigated by flow cytometry and immunofluorescence staining of 5-ethynyl-2′-deoxyuridine (EdU). Osteoblastic differentiation and mineralization were evaluated in chromogenic alkaline phosphatase (ALP) activity substrate assays, Alizarin red S staining, and RT-PCR analysis of early HBMSCs osteogenic marker expression. We demonstrated that HAMSCs stimulated increased alkaline phosphatase (ALP) activity, mRNA expression of osteogenic marker genes, and mineralized matrix deposition. Moreover, the effect of HAMSCs was significantly inhibited by U0126, a highly selective inhibitor of extracellular signaling-regulated kinase 1/2 (ERK1/2) signaling. We demonstrate that HAMSCs promote osteogenic differentiation in HBMSCs by influencing the ERK1/2 signaling pathway. These observations confirm the potential of HAMSCs as a seed cell for the treatment of bone deficiency.